Pengaruh Kompensasi Finansial, Kepemimpinan Transformasional, Dan Kondisi Lingkungan Kerja Fisik Terhadap Kepuasan Kerja Karyawan Pada PT. Wahyu Utama Lestari - Diaksa, Ida Bagus Try Dharma; Dewi, A.A. Sagung Kartika (E-Jurnal Manajemen; Vol 3 No 9 (2014), 2014)
The purpose of this study was to determine the effect of financial compensation, transformational leadership, and physical working conditions on job satisfaction in employees of PT. Wahyu Utama Lestari. This study used a qualitative research using surveys and questionnaires to 60 respondents. Simultaneously obtained findings that financial compensation variables, transformational leadership, and physical work environment significantly influence the variation in job satisfaction. Other results found that partially can be seen that the variable financial compensation, transformational leadership, and physical work environment positive and significant effect on employee job satisfaction. Finally, transformational leadership variable is the variable that has the most dominant effect on employee job satisfaction.   Keywords : Financial compensation, Transformational Leadership, Physical Work Environment, Job Satisfaction
Keywords: Financial compensation, Transformational Leadership, Physical Work Environment, Job Satisfaction